2005
DOI: 10.1186/1471-2407-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin increases the effectiveness of Apo2L/TRAIL for tumor growth inhibition of prostate cancer xenografts

Abstract: Background: Prostate cancer is a significant health problem among American men. Treatment strategies for androgen-independent cancer are currently not available. Tumor necrosis factorrelated apoptosis-inducing ligand (Apo2L/TRAIL) is a death receptor ligand that can induce apoptosis in a variety of cancer cell lines, including androgen-independent PC3 prostate carcinoma cells. In vitro, TRAIL-mediated apoptosis of prostate cancer cell lines can be enhanced by doxorubicin and correlates with the downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…However, a clinical phase I study with Apo2L/TRAIL in a single agent setting has been started in the fall of 2004 (A Ashkenazi, personal communication). Provided a hopefully positive outcome for this study, Apo2L/TRAIL could be another potential candidate for combination with DNA-damaging treatments (Rohn et al, 2001;Belka et al, 2003Belka et al, , 2004El-Zawahry et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…However, a clinical phase I study with Apo2L/TRAIL in a single agent setting has been started in the fall of 2004 (A Ashkenazi, personal communication). Provided a hopefully positive outcome for this study, Apo2L/TRAIL could be another potential candidate for combination with DNA-damaging treatments (Rohn et al, 2001;Belka et al, 2003Belka et al, , 2004El-Zawahry et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Because c-FLIP is a well-known inhibitor of caspase 8 activation and its degradation following drug treatment releases caspase 8 for activation ( 23,24 ), we next determined whether FASN overexpression affects drug-induced degradation of c-FLIP using Western blot analysis. As shown in supplementary It has also been shown that doxorubicin increases PI3K-dependent AKT phosphorylation/activation as early as 1 h with a peak at 24 h ( 26 ).…”
Section: Fasn Overexpression Has No Effect On C-flip Level and Akt Acmentioning
confidence: 99%
“…This finding created great interest and suggested TRAIL or anti-DR5 antibodies, respectively, as potential anticancer drugs (Fulda and Debatin, 2004). Although TRAIL or DR5-antibodies showed only modest effects on experimental tumors, recent studies combining TRAIL with radiation or chemotherapeutic drugs, for example alkylphosphocholines or substances inducing DNAbreakage (Belka et al, 2001(Belka et al, , 2004Rohn et al, 2001;Jendrossek et al, 2002Jendrossek et al, , 2003El-Zawahry et al, 2005) revealed very effective induction of apoptosis and suggest that TRAIL or anti-DR5 antibodies might be used in combination with further chemotherapeutic drugs and/or irradiation.…”
Section: Introductionmentioning
confidence: 99%